Acute cholecystectomies. Indications and technique: about 100 cases of acute cholecystitis - Marella, Muzio S; Trostchansky, José; Olazábal, Alberto (Cirugía del Uruguay, 1973)
-The authors present a hundred cases oi acute cholecystitis. I'hey develop the pathological concept about che e.O.A, and establish the judgments of convenient operation according ti two concepts: a) Concept of time wich allows us to distinguish three surgical peeriods: 1st. Early or opportune peeriod; before the 5th. day; 2nd. intermediate period, between the 5th. and 12th day; 3rd. late period, after the 12 days. b) Concept of evolution, time clinics and paraclinics indexes are enumerated, wich lead to the surgical suggestion. -The importance of the balance and treatment preoperative of the patient is remarked. -The principal lineaments of the complete operation to make in the e.O.A. are noted. -Cholecystectomy from fundus to neck, subserous, cystic cathe terism, drainage transcystic of choledochus simple manometda, cholangiography and aspirated subhepatic drainage. This is the op!ration to perform, when the general and local conditions are allowed, which is almost always possible before the 5th day of evolution of the_ e.O.A. -It is noted the circunstances in which the complete operative plan must be limited to avoid risks to the patient. -The analysis of the results let us take as consequences that the e.O.A. has not mortality before the 5th. day of evolution and the cholecystectomy is the correct operation in that period,